2015
DOI: 10.1111/btp.12250
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tree Genotypic Diversity and Species Diversity on the Arthropod Community Associated with Big‐leaf Mahogany

Abstract: Despite potential interactive effects of plant species and genotypic diversity (SD and GD, respectively) on consumers, studies have usually examined these effects separately. We evaluated the individual and combined effects of tree SD and mahogany (Swietenia macrophylla) GD on the arthropod community associated with mahogany. We conducted this study within the context of a tree diversity experiment consisting of 74 plots with 64 saplings/plot. We sampled 24 of these plots, classified as monocultures of mahogan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 34 publications
(104 reference statements)
1
18
1
4
Order By: Relevance
“…The former could have mediated the observed tree diversity effects on spiders, as previous work in this plantation reported that mahogany plants in polycultures have higher species richness of insect herbivores relative to mahogany monocultures (Campos‐Navarrete et al . ). Future work is necessary to determine the influence of prey availability relative to other abiotic factors ( e.g., canopy openness and temperature; Gunnarsson , Wise ) and habitat complexity (Uetz ) affecting spider recruitment to tree stands.…”
Section: Discussionmentioning
confidence: 97%
“…The former could have mediated the observed tree diversity effects on spiders, as previous work in this plantation reported that mahogany plants in polycultures have higher species richness of insect herbivores relative to mahogany monocultures (Campos‐Navarrete et al . ). Future work is necessary to determine the influence of prey availability relative to other abiotic factors ( e.g., canopy openness and temperature; Gunnarsson , Wise ) and habitat complexity (Uetz ) affecting spider recruitment to tree stands.…”
Section: Discussionmentioning
confidence: 97%
“…While we compared the magnitude of plant species and genetic diversity effects on arthropods when these effects were explored within the same study, we were not able to explore potential interactions between plant species and genetic diversity effects because only a handful of studies had incorporated such interactive effects within the experimental design by manipulating plant genetic diversity at different levels of plant species diversity and vice versa (Campos‐Navarrete, Munguia‐Rosas, Abdala‐Roberts, Quinto, & Parra‐Tabla, ; Crawford & Rudgers, ; Hahn et al., ). These results from the above studies suggest that the species richness of plant communities can modify the effects of plant genetic diversity on arthropods.…”
Section: Discussionmentioning
confidence: 99%
“…; Campos‐Navarrete et al . ). It is unknown, however, whether such genetic differences warrant differential niche occupation and resource use among genetic individuals within the same species – a prerequisite for true complementarity effects (Tilman, Isbell & Cowles ).…”
Section: Introductionmentioning
confidence: 97%
“…Recent research has also repeatedly demonstrated that genotypes within the same species are ecologically differentiated (see Whitham et al 2012;Fischer et al 2014), and this diversity has predictable effects on ecological communities (e.g. Wimp et al 2005;Cook-Patton et al 2011;Zytynska et al 2011;Bangert et al 2013;Busby et al 2013;McArt & Thaler 2013;Abdala-Roberts & Mooney 2014;Barton et al 2015;Campos-Navarrete et al 2015). It is unknown, however, whether such genetic differences warrant differential niche occupation and resource use among genetic individuals within the same speciesa prerequisite for true complementarity effects (Tilman, Isbell & Cowles 2014).…”
Section: Introductionmentioning
confidence: 99%